The greatest ballpark ever : Ebbets Field and the story of the Brooklyn Dodgers - McGee, Bob, 1952- (Rutgers University Press, 2005)
Generations after its demise, iconic Ebbets Field remains the single most colorful and enduring image of a baseball park, with a treasured niche in the game's legacy and the American imagination. In this lively story of sports, politics, and the talented, hilarious, and charming characters associated with the Brooklyn Dodgers, Bob McGee chronicles the ballpark's vibrant history from the drawing board to the wrecking ball, beginning with Charley Ebbets and the heralded opening in 1913, on through the storied eras that followed. McGee weaves a story about how Ebbets Field's architectural details, notable flaws, and striking facade brought Brooklyn and its team together in ways that allowed each to define the other. The author, who puts Dodgers fans in the driver's seat, illustrates poignant examples of how the people who came to play and those who watched and rooted both managed to inspire, endear, and captivate a nation. Ebbets Field was hallowed ground, a cherished place that continues to resonate in memory, long after the walls came down and the cheers subsided. Drawing on original interviews and letters, as well as published and archival sources, The Greatest Ballpark Ever explores the individual struggle of Charley Ebbets to build Ebbets Field, the days of Wilbert Robinson's early pennant winners, the era of the Daffiness Boys, Larry MacPhail and the tumultuous field leadership of Leo the Lip, Branch Rickey and the fiery triumph of Jackie Robinson, the golden days of the Boys of Summer, and Walter O'Malley's ignominious departure. Memorable personalities including Casey Stengel, Zach Wheat, Dazzy Vance, Babe Herman, Van Lingle Mungo, Frenchy Bordargaray, Dolf Camilli, Pistol Pete Reiser, Pee Wee Reese, Mickey Owen, Hugh Casey, and Cookie Lavagetto are all here, as well as Oisk, Skoonj, Gil, Campy, Newk, the Duke, and many more. With humor and passion, The Greatest Ballpark Ever lets readers relive a day in the raucous ballpark with its quirky angles and its bent right-field wall, with the characters and events that have become part of the nation's folklore.